2016
DOI: 10.3892/mco.2016.819
|View full text |Cite
|
Sign up to set email alerts
|

Back to the start: Evaluation of prognostic markers in gastrointestinal stromal tumors

Abstract: Abstract. The aim of this study was to provide a standardized risk stratification model for gastrointestinal stromal tumors (GISTs) based on tumor localization, tumor size, involved lymph nodes and metastases, as well as mitotic activity and other morphological and molecular markers, in order to improve the risk evaluation scheme for recurrence, metastatic spread and survival for patients with GIST. A total of 201 cases of patients with GIST were investigated according to standardized morphological markers, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
2
8
0
6
Order By: Relevance
“…This observation was in agreement with that of Ahmed et al [9], Klieser et al [10], Lopes et al [11] Alqusous et al [12], Vij et al [13], Yacob et al [14], Din et al [16], Li et al [17], Cao et al [18], Sui et al [19], Tazawa et al [20], Kang et al [21], and Kkrishnappa et al [22]. These are in contrast with the two studies of Antonescu et al [7] and Bhalgami et al [15] which found slightly more in the small intestine than stomach.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This observation was in agreement with that of Ahmed et al [9], Klieser et al [10], Lopes et al [11] Alqusous et al [12], Vij et al [13], Yacob et al [14], Din et al [16], Li et al [17], Cao et al [18], Sui et al [19], Tazawa et al [20], Kang et al [21], and Kkrishnappa et al [22]. These are in contrast with the two studies of Antonescu et al [7] and Bhalgami et al [15] which found slightly more in the small intestine than stomach.…”
Section: Discussionsupporting
confidence: 94%
“…One of the studies conducted in Pakistan, Din et al [16], one from China, Sun et al [19], and one from Korea, Kang et al [21], also found that majority were spindle type (84.7%, 83%, 88.2%), followed by epithelioid cell type (12.5%, 10%, 9.3%), and the minority were mixed spindled-epithelioid cell type (2.7%, 8%, 2.5%). However, the study of Klieser et al [10] in Europe found that the majority were spindle type (61.2%), while the epithelioid cell type (19.4%) was equally found with the mixed spindled-epithelioid cell type (19.4%).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…GISTs can occur at every level of the gastrointestinal tract, but most commonly in the stomach (60-70%), and small intestine (20-30%). Rarely, they can be seen in extragastrointestinal locations, like the omentum, retroperitoneum, and mesentery (1)(2)(3)(4)(5)(6)(7). GISTs occur by neoplastic transformation of the interstitial cell of Cajal, the mesenchymal derived intestinal pacemaker cells (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…These cells specifically express the tyrosine kinase receptor c-kit (CD 117). Although several GISTs show strong histomorphological similarities, they have different immunophenotypes and biological behavior, and this diversity yields various confusing data in the literature (1)(2)(3)(4)(5)(6)(7). The purpose of this study was to determine the clinicopathologic features of 65 GISTs and reveal the pathological factors that negatively influence overall survival.…”
Section: Introductionmentioning
confidence: 99%